2005
DOI: 10.1504/ijep.2005.007387
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear tools for characterising radiological dispersion in complex terrain: evaluation of regulatory and emergency response models

Abstract: Routine operations of a nuclear research reactor and its facilities offer opportunities for collection of rare environmental tracer datasets which can be used for atmospheric dispersion model evaluation studies. The HIFAR reactor near Sydney, Australia, routinely emits the radioactive noble gas 41 Ar, and other radionuclides such as 133 Xe and 135 Xe are also emitted from nearby radiopharmaceutical production facilities. Despite extremely low emission levels of these gases, they are nevertheless detectable u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…LSMC and LINCOM have very similar results for the station LH under all stabilities with LSMC performing slightly better than LINCOM under stable conditions and LINCOM performing better under unstable conditions. Williams et al (2005) showed that NUATMOS was significantly better than LINCOM for the station BT with complex terrain and similarly here, LSMC is also significantly better than LINCOM at BT for all statistics under all stabilities. The most significant difference between the two model combinations for station WS is LSMC performing poorly with FA2 of 40% but slightly better compared to LINCOM's FA2 of 20%.…”
Section: Comparing Lsmc With Lincom and Nuatmossupporting
confidence: 68%
See 1 more Smart Citation
“…LSMC and LINCOM have very similar results for the station LH under all stabilities with LSMC performing slightly better than LINCOM under stable conditions and LINCOM performing better under unstable conditions. Williams et al (2005) showed that NUATMOS was significantly better than LINCOM for the station BT with complex terrain and similarly here, LSMC is also significantly better than LINCOM at BT for all statistics under all stabilities. The most significant difference between the two model combinations for station WS is LSMC performing poorly with FA2 of 40% but slightly better compared to LINCOM's FA2 of 20%.…”
Section: Comparing Lsmc With Lincom and Nuatmossupporting
confidence: 68%
“…Therefore, it was decided that NUATMOS with RIMPUFF would be the best model combination for the emergency response system at ANSTO. More recent model evaluation results of LINCOM/RIMPUFF and NUATMOS/RIMPUFF are reported in a recent study by Williams et al (2005) which serves as a useful benchmark for the evaluation presented here of LSMC/RIMPUFF. The model combinations with RIMPUFF are hereon in known as LINCOM, NUATMOS and LSMC.…”
Section: Atmospheric Dispersion Modelsmentioning
confidence: 99%
“…The RIMPUFF model produces forward time predictions of material dispersion and deposition (forward dispersion analysis) and is capable of using local numerical weather prediction data. The maximum spatial grid resolution is 50 m. The RIMPUFF model has previously been used in evaluation studies at the ANSTO site (Williams et al, 2005). RIMPUFF has been applied to the radioxenon release using Limited Area Prediction System (LAPS) numerical weather data provided by the Melbourne Bureau of Meteorology.…”
Section: Rimpuff Within Argosmentioning
confidence: 99%
“…In this work, the researchers assess the radiological dose resulting from radioactive discharge into the environment by the Pc-Cream98 (Consequences of Release to the Environment Assessment Methodology) computer code. Whereas, there are many researches on radiation assessment by using computational modeling Pc-Cream98 which done by other researches in different parts of the globe [1,2,3,4], so it's a good method for assessing the radiological dose resulting from radioactive discharge into the environment of nuclear facilities.…”
Section: Introductionmentioning
confidence: 99%